THE INTERNET IN SCHOOL - THE RESULTS OF STUDY - RACZYNSKA, Maria (Trends in education, 2008)
The chapter presents the influence of the Internet on the evolution of education. This paper presents the use of the Internet in education. It presents some selected IT adaptations in school.
Keywords: Internet; education; information